Conditional residual lifetimes of coherent systems under double monitoring. Issue 7 (3rd April 2017) - Parvardeh, A.; Balakrishnan, N.; Arshadipour, Azam
ABSTRACT: In this paper, we obtain a mixture representation for the reliability function of the conditional residual lifetime of a coherent system with n independent and identically distributed (i.i.d.) components under double monitoring. We suppose that at time t 1, j components have failed while at time t 2 the system is still alive. Based on these mixture representation, we then study stochastic comparisons of the conditional residual lifetimes of two coherent systems with independent and identical components.